2005
DOI: 10.4039/n04-029
|View full text |Cite
|
Sign up to set email alerts
|

Pitfall trap designs to maximize invertebrate captures and minimize captures of nontarget vertebrates

Abstract: Pitfall traps containing a preservative have become the standard method of sampling for epigeal invertebrates such as carabid beetles and cursorial spiders. However, they often result in high levels of mortality for small mammals and amphibians. We compared the carabid, spider, and vertebrate captures within five pitfall trap types (conventional trap, funnel trap, shallow trap, Nordlander trap, and the ramp trap) to determine the trap type that would reduce vertebrate incidental catch without compromising the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 15 publications
8
37
1
Order By: Relevance
“…The lack of vertebrate bycatch recorded for the Laurent pitfall traps of our study confound any certain conclusions here, however. It is likely that the smaller cup sizes used in our study as compared other work (Lemieux and Lindgren 1999;Pearce et al 2005) contributed to the reduction in vertebrate bycatch. Additional and extensive use of the Nordlander design in the other experiments detailed in this dissertation were also free of vertebrate bycatch.…”
Section: Pitfall Trap Efficacycontrasting
confidence: 38%
See 4 more Smart Citations
“…The lack of vertebrate bycatch recorded for the Laurent pitfall traps of our study confound any certain conclusions here, however. It is likely that the smaller cup sizes used in our study as compared other work (Lemieux and Lindgren 1999;Pearce et al 2005) contributed to the reduction in vertebrate bycatch. Additional and extensive use of the Nordlander design in the other experiments detailed in this dissertation were also free of vertebrate bycatch.…”
Section: Pitfall Trap Efficacycontrasting
confidence: 38%
“…Other studies have shown considerable benefits of the Nordlander design in this regard, however. Although vertebrate bycatch using the Nordlander design has been reported (Lemieux and Lindgren 1999;Pearce et al 2005), two points are relevant. First, the entrance holes in both of these studies were 13 mm in diameter because of interest in capturing large carabid beetles, as contrasted with 6-mm in this experiment, intended for the capture of ants.…”
Section: Pitfall Trap Efficacymentioning
confidence: 99%
See 3 more Smart Citations